2020
DOI: 10.1126/sciadv.aba5933
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation and neuronal repression define familial Alzheimer’s disease

Abstract: Identifying the systems-level mechanisms that lead to Alzheimer’s disease, an unmet need, is an essential step toward the development of therapeutics. In this work, we report that the key disease-causative mechanisms, including dedifferentiation and repression of neuronal identity, are triggered by changes in chromatin topology. Here, we generated human induced pluripotent stem cell (hiPSC)–derived neurons from donor patients with early-onset familial Alzheimer’s disease (EOFAD) and used a multiomics approach … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 109 publications
10
59
0
Order By: Relevance
“…We speculate that perhaps the region is undergoing a transition from a cost-effective network to a random network during the SCD stage and that some unnecessary connections to this brain region may cause interference with memory function. This is consistent with the phenomenon of brain dedifferentiation in aging and disease development ( Goh, 2011 ; Caldwell et al, 2020 ). This is still only our conjecture, and follow-up studies need more experimental evidence to further validate it.…”
Section: Discussionsupporting
confidence: 89%
“…We speculate that perhaps the region is undergoing a transition from a cost-effective network to a random network during the SCD stage and that some unnecessary connections to this brain region may cause interference with memory function. This is consistent with the phenomenon of brain dedifferentiation in aging and disease development ( Goh, 2011 ; Caldwell et al, 2020 ). This is still only our conjecture, and follow-up studies need more experimental evidence to further validate it.…”
Section: Discussionsupporting
confidence: 89%
“…Cellular aging features ( Huh et al., 2016 ; Mertens et al., 2015a , 2018 ; Tang et al., 2017 ; Victor et al., 2014 ) and adult-like neuronal identity of iNs ( Luo et al., 2019 ) are likely critical for the emergence of such phenotypes in sporadic AD neurons, because erasure of aging signatures and re-gaining of fetal identity represents a potent rescue in this study ( Miller et al., 2013 ; Ocampo et al., 2016 ). However, neurons that carry aggressive familial AD mutations still show a similar phenotype when generated from iPSCs ( Caldwell et al., 2020 ). Collectively, for studying age-related vulnerability and mechanisms relevant to AD, iNs have advantages over iPSC models and thus complement isogenic iPSC strategies ( van der Kant et al., 2019 ; Meyer et al., 2019 ; Woodruff et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has proposed E2F4 as a major regulator of most AD-specific gene networks ( 15 ), and other bioinformatics-based studies suggest that E2F4 participates in this disease ( 16-18 ). Moreover, distinct AD-related genes contain E2F transcription factor binding sites ( 19 ), and a genome-wide association study for late onset AD has identified a single nucleotide polymorphism that modifies a DNA binding motif of E2F4 as relevant for the disease ( 20 ).…”
Section: Introductionmentioning
confidence: 99%